Identification and characterization of miRNAs in spleens of sheep subjected to repetitive vaccination - Endika Varela-Martínez; Martin Bilbao-Arribas; Naiara Abendaño; Javier Asín; Marta Pérez; Lluís Luján; Begoña M. Jugo (Scientific Reports, 2023)
Abstract Accumulative evidence has shown that short non-coding RNAs such as miRNAs can regulate the innate and adaptive immune responses. Aluminium hydroxide is a commonly used adjuvant in human and veterinary vaccines. Despite its extended use, its mechanism of action is not fully understood and very few in vivo studies have been done to enhance understanding at the molecular level. In this work, we took advantage of a previous long-term experiment in which lambs were exposed to three different treatments by parallel subcutaneous inoculations with aluminium-containing commercial vaccines, an equivalent dose of aluminium or mock injections. Spleen samples were used for miRNA-seq. A total of 46 and 16 miRNAs were found differentially expressed when animals inoculated with commercial vaccines or the adjuvant alone were compared with control animals, respectively. Some miRNAs previously related to macrophage polarization were found dysregulated exclusively by the commercial vaccine treatment but not in the aluminium inoculated animals. The dysregulated miRNAs in vaccine group let-7b-5p, miR-29a-3p, miR-27a and miR-101-3p are candidates for further research, since they may play key roles in the immune response induced by aluminium adjuvants added to vaccines. Finally, protein–protein interaction network analysis points towards leucocyte transendothelial migration as a specific mechanism in animals receiving adjuvant only.